Dynamics simulation of soil carbon in a small rural watershed by Century model - Lopes, Fabíola; Merten, Gustavo Henrique; Mielniczuk, João; Tornquist, Carlos Gustavo; Oliveira, Elisandra Solange (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this study was to combine the Century model with geoprocessing and remote sensing techniques, in order to evaluate spatial-temporal dynamics in total organic carbon (TOC). The study was carried out in a small rural watershed in Northeastern of Rio Grande do Sul State, Brazil. The area was initially under forest cover, which was progressively converted to agriculture in a period of 80 years. The proper calibrating of the model, especially in terms of TOC decomposition parameters, during the initial years of tillage, was essential to produce a coherent simulation of TOC values. Regarding the spatial distribution of TOC, it was observed that greatest impact of soil management on original contents occurred in the areas under cultivation since 1925, which showed a decline of 58.2% in TOC. The Century model integration with a geographic information system makes it possible the study of spatial-temporal dynamics of TOC and the performing of TOC distribution inventories.